Penerapan teknik low impact development (LID) untuk optimalisasi sistem drainase (studi kasus: Kecamatan Cianjur) - Sururi, Mohamad Rangga; Badrukamal, Lingga Rendragraha; Djembarmanah, Rachmawati Sugiharti; Fadlurrohman, Fauzi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
Cianjur District often experiences flooding caused by high rainfall, limited water infiltration in catchment areas, and imbalance between development rate and inadequate drainage system capacity. To address this challenge, this study proposes the application of Low Impact Development (LID) as a solution to reduce flood risk. Hydrological analysis was carried out using rainfall and runoff data to calculate the volume of water flow in existing conditions and LID application scenarios. The simulation used Storm Water Management Model (SWMM) software version 5.2 with 3 scenarios; 1) scenario without LID which produces a runoff discharge of 8,748.26 m3/s; 2) scenario using rain barrel produces 7,318.28 m3/s; and 3) scenario combination of rain barrel and retention ponds which reduce the value to be 118, 28 m3/s. The third scenario is the most effective option as a drainage management strategy in Cianjur District.